CULTIVATING LINGUISTIC COMPETENCE IN THE SPIRIT OF ISLAMIC HIGHER EDUCATION: A CSE-UCLA-BASED EVALUATION OF THE ARABIC LANGUAGE DEVELOPMENT PROGRAM - Mahmudi, Ihwan; Sista, Taufik Rizki; Saifulloh, Ahmad; FADILAH, SITI (JURNAL EDUSCIENCE, 2025)
Purpose - This research aims to evaluate the effectiveness of the Arabic Language Development Program at the University of Darussalam Gontor by reviewing the alignment between institutional objectives, program planning, field implementation, and achieved outcomes within the context of pesantren-based Islamic higher education.Methodology - This research uses a Sequential Explanatory Mixed-Method design, beginning with the quantitative stage through the use of a structured evaluation checklist to assess four components of the CSE-UCLA model (Need Assessment, Planning, Implementation, and Outcomes), then continuing with the qualitative stage through semi-structured interviews, observation, and document analysis to explain and validate the quantitative results. The research participants consist of relevant stakeholders in the management and implementation of the Arabic language program, with qualitative data analysis conducted using a thematic approach.Findings - The findings show that the Need Assessment and Planning aspects are in the category of very good, with strong alignment between the institutional vision, program rationale, and curriculum design. However, there is a gap in the Implementation stage, which is influenced by variations in student abilities, the dynamics of academic–pesantren activities, and the limitations of productive assessment instruments. Nevertheless, the summative evaluation indicates that the program has a significant impact on improving students’ academic competence and strengthening the institution's scientific identity.Contribution - This research contributes to the expansion of the application of the CSE-UCLA evaluation model in the context of Islamic higher education, and provides policy recommendations for strengthening performance-based assessment, harmonizing academic–pesantren environments, and improving program quality in a sustainable manner.